2013
DOI: 10.4236/apd.2013.23016
|View full text |Cite
|
Sign up to set email alerts
|

Biological sources of L-DOPA: An alternative approach

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…La L-DOPA de fuentes naturales reduce los efectos secundarios en los pacientes de la enfermedad de Parkinson, además de tener un costo más bajo y retardar la progresión de la enfermedad en relación con la L-DOPA sintetizada químicamente (Patil et al, 2013). Con todo y esto se requeriría del inhibidor de la DOPA descarboxilasa para evitar que se convierta rápidamente a dopamina fuera del cerebro, y permitir que aumente su biodisponibilidad a nivel central (Menéndez-González et al, 2016).…”
unclassified
“…La L-DOPA de fuentes naturales reduce los efectos secundarios en los pacientes de la enfermedad de Parkinson, además de tener un costo más bajo y retardar la progresión de la enfermedad en relación con la L-DOPA sintetizada químicamente (Patil et al, 2013). Con todo y esto se requeriría del inhibidor de la DOPA descarboxilasa para evitar que se convierta rápidamente a dopamina fuera del cerebro, y permitir que aumente su biodisponibilidad a nivel central (Menéndez-González et al, 2016).…”
unclassified
“…Earlier reports (Nagatsu et al, 1964;Peaston and Weinkove, 2004;Miller et al, 2009) indicated that L-DOPA is an important precursor for the various neurotransmitters like dopamine (Upadhyay et al 2012), noradrenaline and adrenaline collectively known as catecholamines (Gautam et al 2012). Synthesized L-DOPA is expensive and often causes a variety of side effects including nausea, vomiting, low blood pressure, drowsiness, and restlessness (Lee et al, 1996;Knowles, 2003;Patil et al, 2013). Synthesized L-DOPA is expensive and often causes a variety of side effects including nausea, vomiting, low blood pressure, drowsiness, and restlessness (Lee et al, 1996;Knowles, 2003;Patil et al, 2013).…”
mentioning
confidence: 99%
“…Commonly, PD patients are treated with synthesized L-DOPA. Therefore consuming natural sources of L-DOPA to avert potential side effects has been recommended Patil et al, 2013). Therefore consuming natural sources of L-DOPA to avert potential side effects has been recommended Patil et al, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations